Effects of individual and combined caffeine and nitrate supplementation on anaerobic exercise capacity in highly trained judo athletes - preliminary results - Kaszuba, M.; Gren, A.; Helbin, J.; Skotniczny, K.; Kostrzewa, M.; Gawelczyk, M.; Filip-Stachnik, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: There is a strong evidence base for the effectiveness of caffeine and nitrate supplementation on sports performance. Although performance-enhancing benefits have been observed with both caffeine and nitrates used separately, it is unclear whether their combined use has an additive effect. Therefore, the aim of this study was to investigate the effect of individual and combined caffeine and nitrate intake on the anaerobic performance of highly trained judo athletes in both upper and lower body, replicating the combat conditions of the athletes. METHODS: Twenty-five highly trained judo athletes (age: 20 ± 2 years, body mass: 75.9 ± 8.9 kg) habituated to caffeine (2.2 mg/kg/day) participated in a randomized, double-blind, placebo-controlled, parallel-group experiment. Each participant was randomly assigned to one of the following groups: (a) a caffeine placebo (PLAC-CAF) + a beetroot juice placebo (PLAC-BJ) [n=6]; or (b) 6 mg/kg body mass (BM) of caffeine (CAF) + PLAC-BJ [n=4]; or (c) beetroot juice (BJ) + PLAC-CAF [n=7]; or (d) CAF + BJ [n=8]. In each condition athletes ingested 2 x 70 ml of concentrated beetroot juice containing either 400 mg of nitrate or no nitrate for 2 days and 2 × 70 ml 2.5 h prior to each test session. Caffeine or placebo tablets were administered 45 min before the test session. Each session consisted of four 30-s Wingate tests performed with a constant load equivalent to 4.5% and 7.5% of BM for the upper and lower body, respectively. The subjects first performed the upper body test and then, after 1 minute of passive rest, started the lower body test. This protocol was repeated after 3 minutes of passive rest. RESULTS: The two-way repeated measures ANOVA (4 substance 2 Wingate tests) did not show any significant interactions for Relative Peak Power Output (for upper body Wingate test (UBW): p=0.342 and lower body Wingate test (LBW): p=0.143), Fatigue Slope (for UBW: p=0.723 and LBW: p=0.188), Total Work (for UBW: p=0.131 and LBW: p=0.131), nor main effects of group on Relative Peak Power Output (for UBW: p=0.445 and LBW: p=0.532), Fatigue Slope (for UBW: p=0.366 and LBW: p=0.604) and Total Work (for UBW: p=0.131 and LBW: p=0.69). However, it showed significant main effects of the time on Relative Peak Power Output (for UBW: p